Effects of Y2O3–RE2O3 (RE = Sm, Gd, Lu) additives on electrical and mechanical properties of SiC ceramics containing Ti2CN. Issue 12 (September 2016) - Jang, Seung Hoon; Kim, Young-Wook; Kim, Kwang Joo
Abstract: Dense SiC–Ti2 CN composites were fabricated from β-SiC and 4 vol% TiN powders with 2 vol% equimolar Y2 O3 –RE2 O3 (RE = Sm, Gd, Lu) additives by conventional hot pressing. Electrical and mechanical properties of the SiC–Ti2 CN composites were investigated with a variation of sintering additive composition. Relative densities of ∼99.9% were achieved for all specimens. All specimens exhibited electrical resistivities on the order of ∼10 −5  Ω m. These low electrical resistivities were attributed to heavy nitrogen doping in the SiC lattice (carrier density ∼10 20  cm −3 ). Typical electrical resistivity, flexural strength, fracture toughness, and Vickers hardness values of the SiC–Ti2 CN composite sintered with 2 vol% Y2 O3 –Lu2 O3 additives were 2.2 × 10 −5  Ω m, 722 MPa, 4.6 MPa m 1/2, and 25 GPa, respectively.